2021
DOI: 10.15640/jpesm.v8n1a3
|View full text |Cite
|
Sign up to set email alerts
|

Greek Basketball Referees Performance and Stress Factors During and After the Games

Abstract: The purpose of this study was to evaluate the level of pre-competitive anxiety experienced by N=348 Greek basketball referees. In order to classify the stress factors Competitive State Anxiety Inventory-2 (CSAI-2) used. The aim was to examine Cognitive state anxiety, Somatic state anxiety, and Self-confidence, which require them to exercise self-control for optimal performance before and after the games. Results indicated that cognitive and somatic anxiety after the event was higher. On the other hand, self-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The test results showed that the correlation coefficient representing the consistency between the two tests and the split-half coefficient representing the consistency before and after the comprehensive test reached 0.9339 and 0.9322, respectively. 10 They all achieved P<0.01. This indicates that the result is at a very significant level.…”
Section: Discussionmentioning
confidence: 87%
“…The test results showed that the correlation coefficient representing the consistency between the two tests and the split-half coefficient representing the consistency before and after the comprehensive test reached 0.9339 and 0.9322, respectively. 10 They all achieved P<0.01. This indicates that the result is at a very significant level.…”
Section: Discussionmentioning
confidence: 87%
“…The competencies of coaches were grouped into four competency dimensions known as the Coaching Competency Scale (CSS) (Myers, Beauchamp, & Chase, 2011). Moreover, research results (Ntasis, Panagi, Strigas, Koronios, & Dashi, 2021) concluded that coaches had four competencies. According to (Moen, Federici, & Klemetsen, 2014), the grouping of competencies of coaches is divided into six dimensions of competence.…”
Section: Discussionmentioning
confidence: 99%